2005
DOI: 10.1007/s00383-005-1594-3
|View full text |Cite
|
Sign up to set email alerts
|

Rectovestibular fistula with vaginal malformations

Abstract: Anorectal malformations are associated with other anomalies among which vaginal malformations are occasionally encountered and may go unnoticed by the primary physician. Between January 1998 and December 2003, 563 cases of anorectal malformations were managed in Pediatric Surgery Department, Chittagong Medical College & Hospital, Chittagong, Bangladesh. Among these, five cases of rectovestibular fistula were associated with vaginal malformations. In this retrospective study age, physical findings, operative fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…The treatment modalities used in the 22 cases of vestibular fistula with absent vagina, reported in the literature [3,[6][7][8][9]11,[15][16][17][18], included 8 vaginal replacements with rectum, 3 replacements with sigmoid, 3 successful vaginal mobilization in cases of distal vaginal atresia, 2 replacements with small bowel, and 1 with skin flaps. No information was found related to the vaginal reconstruction in the remaining 5 cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment modalities used in the 22 cases of vestibular fistula with absent vagina, reported in the literature [3,[6][7][8][9]11,[15][16][17][18], included 8 vaginal replacements with rectum, 3 replacements with sigmoid, 3 successful vaginal mobilization in cases of distal vaginal atresia, 2 replacements with small bowel, and 1 with skin flaps. No information was found related to the vaginal reconstruction in the remaining 5 cases.…”
Section: Discussionmentioning
confidence: 99%
“…When treated appropriately, these patients have an excellent functional prognosis for bowel and urinary control [1]. In a review of the literature, we found that associated gynecologic defects are rarely mentioned [2][3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O impacto do nascimento de uma criança mal formada é profundo, aliado ao problema da imperfuração anal inclui, aos pais e familiares, o desapontamento, a vergonha, os complexos de culpa, acusações mútuas, rejeições, preocupações financeiras e o medo das futuras gestações (3)(4)7) . A imperfuração anal é uma das anomalias anorretais e está associadas aos defeitos em outros sistemas do corpo (3,8) , e estudos mostram a associação mais frequente com o trato urogenital (9)(10)(11)(12)(13)(14) ; a sobrevida depende da severidade das anomalias associadas. Logo no início deve-se obter uma anamnese sistemática e iniciar o tratamento, cirúrgico ou clínico, o mais precoce possível, a lesão se desenvolve devido à falta de complementação do complexo embriológico (15)(16)(17)(18)(19) .…”
Section: Resul Resul Resul Resul Results T T T Tado Ado Ado Ado Ados Sunclassified
“…Rectovestibular fistula is found exclusively in females and is of congenital in nature [2]. This is often confused with rectovaginal fistula which is found in less than 1% cases [3]. There is no definitive causative factor noted in this anomaly but the drugs used during pregnancy are thought to be one of the reasons for this anomaly.…”
Section: Discussionmentioning
confidence: 99%